2010
DOI: 10.1051/0004-6361/200913628
|View full text |Cite
|
Sign up to set email alerts
|

All-sky Galactic radiation at 45 MHz and spectral index between 45 and 408 MHz

Abstract: Aims. We study the Galactic large-scale synchrotron emission by generating a reliable all-sky spectral index map and temperature map at 45 MHz. Methods. We use our observations, the published all-sky map at 408 MHz, and a bibliographical compilation to produce a map corrected for zero-level offset and extragalactic contribution. Results. We present full sky maps of the Galactic emission at 45 MHz and the Galactic spectral index between 45 and 408 MHz with an angular resolution of 5• . The spectral index varies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(164 citation statements)
references
References 57 publications
7
155
2
Order By: Relevance
“…8 that beam correction has a significant impact on the recovered spectral index. Without correction, the beam effects mask the flattening that is expected near the Galactic Centre (de Oliveira-Costa et al 2008;Guzmán et al 2011).…”
Section: Spectral Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…8 that beam correction has a significant impact on the recovered spectral index. Without correction, the beam effects mask the flattening that is expected near the Galactic Centre (de Oliveira-Costa et al 2008;Guzmán et al 2011).…”
Section: Spectral Indexmentioning
confidence: 99%
“…Both the Haslam map and the GSM have become widely used and cited in both simulations and data reduction pipelines for redshifted 21 cm observations (Bowman, Morales, & Hewitt 2009;Patra et al 2013;Subrahmanyan & Cowsik 2013;Thyagarajan et al 2015;Bernardi et al 2016). Guzmán et al 2011 created an all-sky temperature map at 45 MHz based upon the surveys of Alverez et al (1997) and Maeda et al (1999). In addition, they produced an allsky Galactic spectral index map based upon two frequency points by using their 45 MHz and the Haslam 408 MHz map after corrections for zero-level, extragalactic non-thermal emission, and CMB factors.…”
Section: Introductionmentioning
confidence: 99%
“…A correction factor (Tgal+Tsys)/Tsys is used to scale the flux densities at these frequencies where Tsys corresponds to the system temperature associated with the flux calibrators. Tgal is estimated by extrapolating the sky temperature value at 408 MHz (Haslam et al 1982) to 325 and 610 MHz assuming a spectral index of −2.6 (Roger et al 1999; Guzmán et al 2011) for the Galactic plane emission. The correction factors estimated this way are used to scale the images.…”
Section: Gmrt Observations and Data Reductionmentioning
confidence: 99%
“…Thus the constancy of the mean spectral index between 408 MHz and the 2300 MHz can be given directly for the entire GEM strip, irrespective of emission region, and results in −2.64 ± 0.11 according to the Rhodes survey and −2.63 ± 0.21 according to the GEM survey. Guzman et al (2011) have also recently reported a temperature spectral index of −2.5 to −2.6 over most of the sky between 45 MHz and 408 MHz. On the other hand, when the mean spectral index of the GEM and Rhodes surveys is obtained with respect to the WMAP K-band, the steepening of the spectral index increases toward the low-emission region, as expected for relativistic electrons of higher energies propagating to the larger scale heights that characterize these regions at high Galactic latitudes.…”
Section: Temperature Spectral Indexmentioning
confidence: 86%